A combined association test for rare variants using family and case-control data. Issue 7 (October 2016) - Lin, Peng-Lin; Tsai, Wei-Yun; Chung, Ren-Hua
Abstract Statistical association tests for rare variants can be classified as the burden approach and the sequence kernel association test (SKAT) approach. The burden and SKAT approaches, originally developed for case–control analysis, have also been extended to family-based tests. In the presence of both case–control and family data for a study, joint analysis for the combined data set can increase the statistical power. We extended the Combined Association in the Presence of Linkage (CAPL) test, using both case–control and family data for testing common variants, to rare variant association analysis. The burden and SKAT algorithms were applied to the CAPL test. We used simulations to verify that the CAPL tests incorporating the burden and SKAT algorithms have correct type I error rates. Power studies suggested that both tests have adequate power to identify rare variants associated with the disease. We applied the tests to the Genetic Analysis Workshop 19 data set using the combined family and case–control data for hypertension. The analysis identified several candidate genes for hypertension.